Psychological stressors of imprisonment and coping of older incarcerated persons: a qualitative interview study - Stuart McLennan; Leila Meyer; Tenzin Wangmo; Jens Gaab; Bernice Elger; Helene Seaward (BMC Public Health)
Abstract Background Imprisonment has a major impact on a person’s psychological well-being. The proportion of older imprisoned persons is dramatically increasing worldwide, and they are likely to have greater physical and mental health needs compared to younger persons in prisons. However, there is currently a lack of research on the psychological stressors and the coping strategies of older imprisoned persons. This study therefore aims to explore the key psychological stressors experienced by older imprisoned persons and their coping strategies. Methods Individual semi-structured qualitative interviews were conducted between April 2017 and December 2018 with a purposive sample of 79 participants from 2 different groups in Switzerland: older imprisoned persons (n = 50) and mental health professionals (n = 29) with experience working in prisons. Transcripts were analysed using conventional content analysis. Results This study has identified various ways in which the prison environment not only undermines older incarcerated persons´ psychological well-being, but also their ability to manage the stress they are experiencing. Two overarching psychological stressors identified were a lack of physical and emotional closeness in social relationships (with prison staff, with other incarcerated persons, and outside of prison), and the loss of autonomy in prison. Participants reported five main ways that older incarcerated persons coped with the psychological stressors in prison: 1) recognising a lack of control over situation, 2) withdrawing and isolating, 3) self-improvement, 4) staying connected to the outside world, and 5) self-expression. Conclusions To improve the psychological well-being of older incarcerated persons, there is a need for: specialised training of prison staff regarding hardships that elderly persons can face in prison relationships, encouragement and enablement of social contacts with the outside world, and increasing possibilities for autonomy, new challenges, and thus stimuli within a limited setting.